Formulasi dan Uji Hedonik Serbuk Effervescent Ekstrak Kunyit dengan Variasi Asam Sitrat dan Asam Tartat - Octavia, Devi Ristian; Nurafifah, Dian; Muhtaromah, Muhtaromah; Utami, Primanitha Ria (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Turmeric (Curcuma longa), which is widely grown in tropical Asia, is known to have various health benefits. The use of turmeric is well known, among others, as herbal medicine, whereas as an ingredient in effervescent tablets it has never been developed. This study aims to produce the best formula for making turmeric effervescent powder that the public likes. This research is an experimental research. Turmeric was extracted and then made an effervescent powder with three variations of the formula for citric acid and tartic acid, namely formula 1 (3: 1), 2 (2: 2), and 3 (1: 3). The effervescent powder that has been made was then evaluated for its physico-chemical properties and a hedonic test was carried out on 20 panelists to test their preferences for color, taste, aroma and texture. The data obtained were then analyzed using the SPSS 22 statistical test, using the ANOVA test and Duncan's Post Hoc advanced test. The results showed that all formulas met the criteria for chemical physical properties of effervescent powder drink where the Hedonic test results showed that formula 3 was the most preferred formula by panelists.